Catalyst development for the hydrogen to propylene oxide process with in-situ generated hydrogen peroxide and intensification in a trickle bed reactor - Schmidt, Christoph; Sandri, Francesco; Vidrequin, Alice; Favier, Jeremy; Aho, Atte; Granroth, Sari; Lastusaari, Mika; Salmi, Tapio (Elsevier, 2026)
Novel continuous propylene oxide production via in-situ generated hydrogen peroxide under mild liquid phase conditions was optimized by tailoring gold-palladium on titanium silicalite 1 (TS-1) catalysts and reaction parameters. AuPd alloy nanoparticles were deposited on two commercial TS-1 supports, with and without anatase impurities. On anatase-free TS-1, highly dispersed AuPd nanoparticles (6–10 nm) were formed, whereas in anatase-containing TS-1, metal precursors preferentially deposited on anatase, yielding larger nanoparticles after calcining. Ammonium hydroxide and water, water-only washing, and no washing were applied after synthesis, with water-only washing yielding smallest nanoparticles. Prolonged urea-deposition synthesis promoted metal redispersion, confirmed by material sampling during synthesis, and improved catalyst stability. In the combined direct synthesis of hydrogen peroxide and hydrogen peroxide to propylene oxide process (HPPO), smaller AuPd nanoparticles enhanced propylene oxide production but decreased propylene oxide selectivity by formation of propane and ring-opening products. Au-richer alloys improved propylene oxide selectivity but decreased propylene oxide productivity, while monometallic gold was inactive in the reaction system. Higher metal loadings increased propylene oxide productivity only for gold-richer alloys. Reaction parameter optimization identified that higher temperature and reduced liquid flow rate favored hydrogen peroxide conversion and ring-opening products formation, while shifting from propene-rich to oxygen-rich feed suppressed propane formation.